CEH Certified Ethical Hacker exam guide exam guide - Walker, Matthew (McGraw-Hill Education, 2014)
Fully updated for the CEH v8 exam objectives, this comprehensive guide offers complete coverage of the EC-Council's Certified Ethical Hacker exam. In this new edition, IT security expert Matt Walker discusses the latest tools, techniques, and exploits relevant to the CEH exam. You'll find learning objectives at the beginning of each chapter, exam tips, practice exam questions, and in-depth explanations. Designed to help you pass the exam with ease, this authoritative resource also serves as an essential on-the-job reference.